Hedge accounting no mercado acionário brasileiro : efeitos na qualidade da informação contábil e disclosure - Potin, Silas Adolfo (2014)
This work investigates, in the Brazilian stock market, the effect of hedge accounting on the quality of accounting information disclosed, in the disclosure of derivative financial instruments and information asymmetry. To measure the quality of accounting information, the metrics of relevance of accounting information and accounting earnings informativeness were used. For the execution of this work, a general sample consisted of non-financial Brazilian companies, listed on São Paulo’s Stock Market, comprising 150 companies with the highest market value in 01/01/2014. From the overall sample, samples were set up for the implementation of models of value relevance, informativeness, disclosure and information asymmetry. The relevance sample included 758 firms–years observations for the period ranging from 2008 to 2013. The sample for informativeness included 701 firms–years observations for the period from 2008 to 2013. The sample for disclosure had 100 firms–year observations, for the period from 2011 to 2012. The sample for information asymmetry had 100 firms–years observations for the period 2011 to 2012. For the statistical analysis, we used regressions with robust standard errors with POLS approach and Fixed Effects, applied to panel data. In addition to the analysis of the effect of hedge accounting on the disclosure and information asymmetry, we applied the method of propensity score matching. The evidence for the influence of hedge accounting on the relevance of accounting information showed a positive and significant relationship in the interaction with earnings. In the informativeness of accounting earnings analysis, the research showed a negative and statistically significant relationship between earnings when interacted and the hedge accounting dummy variable. As for the evidence found for the influence of hedge accounting on the disclosure of derivatives, there was a positive and statistically significant relationship between the hedge accounting dummy and the disclosure indicator of derivatives. Regarding evidence for information asymmetry, although the coefficients showed the expected effect, they were not statistically significant. Additionally, we incorporated, to the econometric analyzes, a descriptive analysis, in the overall sample, of the use of hedge accounting in Brazil for 2013. Among the 150 companies in the sample, 49 companies used hedge accounting, where 41 companies adopt only one type hedge. The cash flow hedge is the type of hedge more adopted by companies, being used by 42 companies.